Literature Review: Hubungan Terapi Sensori Integrasi terhadap Perubahan Perilaku dan Konsentrasi Anak ADHD (Attention Deficit Hyperactive Disorder) - Gabrina Watari; Austin Bertilova Carmelita; Lia Sasmithae (Jurnal Surya Medika (JSM), 2021)
Attention deficit hyperactivity disorder (ADHD), a neurobehavioral disorder that most often occurs in children, is a condition that affects school-age children as a mental disorder. One of the therapies that can be used is integrated sensory therapy with a form of therapy that encourages a child to develop their physical abilities. Search this article to see the relationship of integrated sensory therapy to changes in behavior and concentration of children with ADHD (Attention Deficit Hyperactive Disorder). Searching for articles through google scholar, found 18 journals to be reviewed. There were several games that had a relationship between sensory therapy, integration of behavior changes and concentration of children with ADHD, short-term play increased children's concentration, guessing the contents of the glass increased children's concentration and behavior, socialization games decreased impulsive behavior, bowling increased children's concentration, game education, increased concentration play children, PECS (Picture Exchange Communication System) increases children's concentration, mazes increase concentration, cranks increase children's concentration, flashcards increase concentration, music increases concentration and decreases impulsive behavior and writing increases concentration and decreases impulsive behavior. There is 1 journal which states that there is no difference between the integrated sensory therapy group and the untreated sensory integration group. There is a relationship between integrated sensory therapy to behavior change and control of children with ADHD. Integration sensory therapy involves activities that manage the sensory system by providing vestibular, proprioceptive, auditory, and touch input so that it can reduce hyperactive behavior and increase constructive behavior in children with ADHD.